MODEL PELAKSANAAN PEMBELAJARAN DARING PADA MASA PANDEMI COVID 19 DI PROVINSI LAMPUNG - Marilin Kristina; Ruly Nadian Sari; Erliza Septia Nagara (Idaarah: Jurnal Manajemen Pendidikan, 2020)
This study aims to determine the implementation model of online learning during the COVID-19 pandemic in Lampung. This online learning was carried out because of the corona virus outbreak 19. The samples of this study were public and private elementary, middle and high school students in Lampung. This study used simple random sampling technique by considering population homogeneity. The data instrument used an online learning questionnaire. Data analysis using descriptive statistics. The results illustrate that the most widely used online learning model is the WhatsApp application with 87.2%, Google Classroom 41.3%, Google Meeting or Zoom 13.8%, Youtube 15.6% and other application’s 12.8%. This percentage is obtained from respondents who use more than one online learning application.